PENGUATAN WEWENANG KOMISI YUDISIAL DALAM MENJAGA KEHORMATAN DAN MARTABAT HAKIM DITINJAU DARI UNDANG-UNDANG NOMOR 22 TAHUN 2004 TENTANG KOMISI YUDISIAL - Weo, Joey Giancello; Tuba Helan, Yohanes G; Lamataro, Cyrilius W T (Petitum Law Journal, 2024)
The main point in this issue is how to strengthen the authority of the judicial commission to ensure the honor and dignity of judges? What is an obstacle to strengthening the authority of the judicial commission is maintaining the honor and dignity of judges. This research is a normative juridical research, which is research on applicable legal norms, including research on the level of vertical and horizontal synchronization. The synchronization in question is the laws and regulations relating to the Judicial Commission This conclusion emphasizes the important role of the Judicial Commission as a judge monitoring institution in maintaining the honor and dignity of judges. With a deep understanding of Law Number 22 of 2004, the Judicial Commission can carry out its supervisory function optimally, provide a sense of justice to the public, and strengthen the foundation of the integrity of the judiciary in Indonesia. This understanding also provides direction for improving and updating regulations if necessary in order to respond to the dynamics of legal developments and community needs in the future.